THE ROLE OF PARENTS IN PROVIDING CHILDREN LEARNING FACILITIES TO DEVELOP CREATIVITY - Citra Imelda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This research was motivated by the conditions encountered in the field that: 1)there were still parents who lacked knowledge about what facilities orinfrastructure were given to basic children, 2) still not creating a good learningatmosphere at home. So the purpose of this study is to describe: 1) The role ofparents in creating a good atmosphere at home. 2) The role of parents in providingfacilities and infrastructure in providing child learning facilities. This research isquantitative descriptive. The population of this study were all parents of grade 1elementary school students in RW 01 RT 01 and 02 in Binuang Village, PauhSub-District, Padang City, as many as 32 people. The technique used in samplingis total sampling. The instrument used in this study is a questionnaire, while fortechnical data analysis. The results of this study indicate that: 1) the role ofparents in providing learning facilities for grade 1 children in good aspects, and 2)in the aspects of learning facilities and infrastructure at home are also in goodcategory. Based on the results of this study the researchers can develop more rolesin providing learning facilities for grade 1 elementary school children.